Analisis Perilaku Konsumen Kedai Kopi - Sari, Ni Kadek Mita; Hartati, Putu Sri; Sasmita Dewi, Ida Ayu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Purchase decisions are influenced by many factors, including location, store atmosphere, and lifestyle. The purpose of this study was to determine the effect of location, store atmosphere, and lifestyle on purchasing decisions for coffee shop drinks at Kedai Pica. Kedai Pica was chosen as research site with a population of 12,930 customers and a sample of 99 respondents by accidental sampling. Data was collected by using interviews and questionnaires which were measured using a Likert Scale with five answer choices ranging from strongly disagree with a score of one and strongly agree with a score of five. The instrument test was carried out by testing the validity and reliability, followed by classical assumption testing and hypothesis testing with multiple linear regression analysis using SPSS software. The results of the study prove that location, store atmosphere, and lifestyle has a positive and significant effect on purchasing decisions.